2024
DOI: 10.1038/s41565-023-01585-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and in vivo distribution of mesenchymal-stem-cell-derived extracellular vesicles are protein corona dependent

Revadee Liam-Or,
Farid N. Faruqu,
Adam Walters
et al.

Abstract: Extracellular vesicles (EVs) derived from mesenchymal stem cells are promising nanotherapeutics in liver diseases due to their regenerative and immunomodulatory properties. Nevertheless, a concern has been raised regarding the rapid clearance of exogenous EVs by phagocytic cells. Here we explore the impact of protein corona on EVs derived from two culturing conditions in which specific proteins acquired from media were simultaneously adsorbed on the EV surface. Additionally, by incubating EVs with serum, simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…28 To address this issue, recent studies have enhanced EV targeting by forming a protein corona on their surface, specifically coating C-EVs with albumin to improve delivery to hepatocytes beyond macrophages. 28 Additionally, surface engineering of EVs has been used to enhance targeted delivery to specific cells, thereby enhancing therapeutic efficacy. [29][30][31][32] Our findings prove that SIRP expression on EVs not only mitigates necroptosis but also promotes effective accumulation in CD47-overexpressing liver tissues and hepatocytes extending beyond macrophages in acute inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…28 To address this issue, recent studies have enhanced EV targeting by forming a protein corona on their surface, specifically coating C-EVs with albumin to improve delivery to hepatocytes beyond macrophages. 28 Additionally, surface engineering of EVs has been used to enhance targeted delivery to specific cells, thereby enhancing therapeutic efficacy. [29][30][31][32] Our findings prove that SIRP expression on EVs not only mitigates necroptosis but also promotes effective accumulation in CD47-overexpressing liver tissues and hepatocytes extending beyond macrophages in acute inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Both the intracellularly and extracellularly formed types of protein coronas may be relevant for EVs function [ 51 ]. Interestingly, Liam-Or et al have very recently reported that the composition of the protein corona that wraps EVs dictates crucial properties of these vesicles, including their in vivo distribution as well as their targeting and uptake by specific recipient cells [ 52 ].…”
Section: Integrins In the Docking And Uptake Of Tevsmentioning
confidence: 99%
“…Following administration, the PC will become a responsive structure that can bind to the target site, thereby eliciting the therapeutic effect. 184 Tissues lacking target sites will remain unresponsive to the structure, mitigating potential adverse reactions. Tincu et al applied BSA coronas to NLCs loaded with piperine (Pip) to alter the delivery capacity of NLCs to colon, ovary, and breast cancer cells.…”
Section: Reflections and Perspectives On Future Research Directionsmentioning
confidence: 99%